PERSPEKTIF KRIMINOLOGI DALAM MENGKAJI “PERKOSAAN TERHADAP LAKI-LAKI” Di INDONESIA - Angga Pratama, I Gede; Gatrawan, I Nyoman (Kertha Negara : Journal Ilmu Hukum, 2015)
Rape case usually is identiced with rape of women. Where as in the reality the rape is not only happened to women, actually men also experienced the same thing. Rape of men also included in penal act which breaks decency. But in our Criminal Code is meant as a situation which only happens to a woman only, it is seen in Article 285 Criminal Code of Indonesia. From this background is taken problem, How does the criminology perspective in studying rape of men in Indonesia. The writing method that used is normative juridical method by using law approach. The result of this study concludes that needed an expands to define the rape from Article 285 Criminal code that is not only rule about rape of women but also rape of men.
Keywords: Criminology, Male, Rape, Penal Act Decency